Pengaruh Kepercayaan dan Kepuasan Pelanggan terhadap Loyalitas Konsumen Wanita pada Produk Kecantikan Wardah - Eka Prasetya, Dimas; Agus Setyawan, Anton (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of customer trust and satisfaction on female consumer loyalty to Wardah beauty products. The approach used was quantitative with an explanatory research method, which focuses on testing the relationship between variables through statistical analysis. The research sample was obtained using a purposive sampling technique based on the criteria of women aged 15 years and over who have purchased Wardah products at least twice. Primary data were collected through an online questionnaire using a five-point Likert scale. Data analysis was performed using multiple linear regression at a significance level of 5%. The results showed that customer trust and satisfaction variables have a positive and significant effect on customer loyalty. This indicates that the higher the level of trust and satisfaction felt by consumers, the greater their tendency to remain loyal to Wardah products. These findings have implications for companies to continue strengthening their educational marketing communication strategies and improving customer loyalty programs to maintain long-term relationships with consumers.